Evidence for dynamic resource partitioning between two sympatric reef shark species within the British Indian Ocean Territory. Issue 4 (11th April 2019) - Curnick, David J.; Carlisle, Aaron B.; Gollock, Matthew J.; Schallert, Robert J.; Hussey, Nigel E.
Abstract : Stable‐isotope analyses (δ 13 C, δ 15 N and δ 34 S) of multiple tissues (fin, muscle, red blood cells and plasma), revealed ontogenetic shifts in resource use by grey reef sharks Carcharhinus amblyrhynchos and resource partitioning with silvertip sharks Carcharhinus albimarginatus within the British Indian Ocean Territory marine protected area (MPA). Resource partitioning varied temporally, with C. albimarginatus feeding on more pelagic prey during October to January, potentially attributable to an influx of pelagic prey from outside the MPA at that time. Reef sharks may therefore be affected by processes outside an MPA, even if the sharks do not leave the MPA.